Sharing and Safeguarding Pediatric Data - Patrinos, Dimitri; Knoppers, Bartha Maria; Laplante, David P.; Rahbari, Noriyeh; Wazana, Ashley (Frontiers in Genetics, 2022)
Data sharing is key to advancing our understanding of human health and well-being. While issues related to pediatric research warrant strong ethical protections, overly protectionist policies may serve to exclude minors from data sharing initiatives. Pediatric data sharing is critical to scientific research concerning health and well-being, to say nothing of understanding human development generally. For example, large-scale pediatric longitudinal studies, such as those in the DREAM-BIG Consortium, on the influence of prenatal adversity factors on child psychopathology, will provide prevention data and generate future health benefits. Recent initiatives have formulated sound policy to help enable and foster data sharing practices for pediatric research. To help translate these policy initiatives into practice, we discuss how model consent clauses for pediatric research can help address some of the issues and challenges of pediatric data sharing, while enabling data sharing.